Sequential contests with incomplete information: Theory and experimental evidence - Brookins, Philip; Matros, Alexander; Tzachrista, Foteini (Journal of economic behavior & organization, 2025)
We investigate behavior in two-player sequential-move contests with complete and incomplete information about the value of the prize. First, we describe a Bayesian equilibrium in which both players have private prize values. Then, we test our predictions in the experimental laboratory. We analyze three settings: symmetric prize valuations with complete information, asymmetric prize valuations with complete information, and asymmetric prize valuations with incomplete information. We find that subjects’ behavior is less consistent with theory and more in line with simple mental shortcuts. Our data supports a simple investment heuristic for each player type. On average, first-movers invest half of their own valuation and second-movers, regardless of their prize valuation, invest frequently in one of the following ways: drop out of the contest or invest at or just above the first-movers’ investment. We add to the growing literature by showing that experimental contest data can be better explained by simple heuristics.